Macromedia Director 8 and Lingo (CD) - Green, Thomas J. (Prima Tech, 2000)
Director is the market-leading multimedia solution for creating engaging, rich corporate media presentations, e-merchandising applications, and entertainment. It is quickly becoming a widely used technology for the development of Web-based multimedia. However, most corporate users and graphic artists don’t want to spend the time learning programming. They would rather just look at the code and take it from there. Macromedia Director 8 and Lingo Fast & Easy Web Development does this by giving you the basic skills and knowledge necessary to go to the next level in Director. It can benefit such users as Web developers, corporate and student users, Web design firms, and game companie